2016
DOI: 10.1002/jrs.4992
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman scattering properties of Lewis acid–base complexes ofp‐hydroxybenzoic andp‐mercaptobenzoic acids with CO2in the presence of silver

Abstract: Effects of local environment on the sensitivity of surface‐enhanced Raman scattering have been recently considered as an important issue in experiments involving charge‐transfer mechanism between the adsorbed molecules and the metal surface. To theoretically investigate this issue, we consider the complexation of p‐hydroxybenzoic acid (PHBA) and p‐mercaptobenzoic acid (PMBA) with carbon dioxide (CO2), and in contact with silver (Ag), by means of ab initio calculations. Within the Møller–Plesset perturbation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Raman scattering proprieties were also calculated for a complementary analysis of active vibrational modes in cold clusters. Depolarization ratios were determined for natural (ρ n ) and plane-polarized (ρ p ) light in a same fashion as we already carried out for similar systems. , As is known in Raman scattering theory, the maximum values of depolarization ratios are ρ p max = 3/4 and ρ n max = 6/7. Thus, for cold oriented carriers with unidentified vibrational emission in laboratory, such as trapped molecules in ice, the depolarization ratios can provide information about the symmetry of the molecule, as well as the vibrational mode assigned to that Raman peak.…”
Section: Methodsmentioning
confidence: 99%
“…Raman scattering proprieties were also calculated for a complementary analysis of active vibrational modes in cold clusters. Depolarization ratios were determined for natural (ρ n ) and plane-polarized (ρ p ) light in a same fashion as we already carried out for similar systems. , As is known in Raman scattering theory, the maximum values of depolarization ratios are ρ p max = 3/4 and ρ n max = 6/7. Thus, for cold oriented carriers with unidentified vibrational emission in laboratory, such as trapped molecules in ice, the depolarization ratios can provide information about the symmetry of the molecule, as well as the vibrational mode assigned to that Raman peak.…”
Section: Methodsmentioning
confidence: 99%
“…Filho, Cunha, and Rivelino studied the SERS properties of the Lewis acid‐base (LA‐LB) complexes of p‐hydroxybenzoic and p‐mercaptobenzoic acids with CO 2 in the presence of silver. Their work demonstrated that the lowest singlet π‐π* excitation of both LA‐LB complexes is significantly red‐shifted, which gives evidence for such a complexation with CO 2 . Kitahama et al described the analysis of blinking from multicolored SERS‐active Ag colloidal nanoaggregates with poly‐L‐lysine by means of a truncated power law.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%